(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2022)
Today’s organizations consider economic, social and cultural aspects for their performance, so the concept of corporate social responsibility has been evolving and serves as a strategy for solving problems arising from any activity. A socially responsible company is one where its products or services are aligned to contribute to the welfare of society. This behavior goes beyond a strict vision for compliance with regulations, it is rather linked to ethical behavior and considering the needs of all those involved in the process. This corporate philosophy adopted by senior management goes beyond ensuring the economic benefit and well-being of workers. In the case of agricultural companies, it seeks to reduce the impact that this activity has on the environment and carry out sustainable agriculture. There are initiatives that seek to institutionalize this practice within organizations regardless of the size or the sector in which they work, in order to develop competitive advantages, meet economic objectives and encourage sustainable development. In addition, these practices improve the company’s reputation and profitability.